Palliative and Supportive Care in the Philippines: Systems, Barriers, and Steps Forward - Ho, Frances Dominique V. (Archīum Ateneo, 2024)
Although integral to alleviating serious health-related suffering, global palliative care remains systemically and culturally inaccessible to many patients living in low- and middle-income countries. In the Philippines, a lower-middle income country in Southeast Asia of over 110 million people, up to 75% of patients with cancer suffer from inadequate pain relief. We reviewed factors that preclude access to basic palliative care services in the Philippines. PubMed and Google Scholar were searched thoroughly; search terms included but were not limited to “palliative care,” “supportive care,” “end-of-life care,” and “Philippines.” We found that a limited palliative care workforce, high out-of-pocket healthcare costs, and low opioid availability all hinder access to palliative care in the archipelago. Religious fatalism, strong family-orientedness, and physician reluctance to refer to palliative care providers represent contributory sociocultural factors. Efforts to improve palliative care accessibility in the country must address health systems barriers while encouraging clinicians to discuss end-of-life options in a timely manner that integrates patients’ unique individual, familial, and spiritual values. Research is needed to elucidate how Filipinos—and other global populations—view end-of-life, and how palliative care strategies can be individualised accordingly.